Efektifitas Transcutaneous Electrical Nerve Stimulation dan Latihan Closed Kinetic Chain Terhadap Penurunan Nyeri Pada Kasus Osteoarthritis Knee di RSU. Bangil - Anang Tri Haryono; Achmad Fariz; Retno Dewi Prisusanti; Agung Hadi Endaryanto; Angria Pradita (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2021)
Osteoarthritis (OA) is a progressive disease that damages the knee joint due to aging. One of the physiotherapy interventions is TENS and closed kinetic chain exercises which are believed to reduce pain. The purpose of this study was to determine the effect of the combination of these two interventions in reducing pain. Types of research  A quasi-experimental design with a one-group pre-post test conducted during September-October 2021 at Bangil General Hospital with a population of 42 people who were taken randomly by meeting the inclusion and exclusion criteria. The number of samples as many as 30 people using the visual analogue scale (VAS) as a measuring tool. Administration of TENS with a frequency of 5 Hz, intensity 30 mA, time 20 minutes, and a dose of 3 sets of CKC exercise, 10 repetitions/set with 15 seconds of rest/set for 4 weeks with 2 visits per week. The hypothesis test used by Wilcoxon was obtained and the median pre and post values were 6.00 and 5.00, respectively, with a significance value of 0.000 (<0.05). It was concluded that the combination of Transcutaneous Electrical Nerves Stimulation (TENS) and Closed Kinetic Chain (CKC) was effective in reducing pain in cases of knee osteoarthritis.Keywords: osteoarthritis; transcutaneous electrical nerves stimulation ; closed kinetic chainABSTRAK Osteoarthritis (OA) adalah penyakit progresif yang merusak sendi lutut akibat faktor penuaan. Salah satu intervensi fisioterapi adalah TENS dan latihan closed kinetic chain yang diyakini dapat mereduksi nyeri. Tujuan penelitian ini untuk mengetahui efek kombinasi kedua intervensi ini dalam menurunkan nyeri. Jenis penelitian quasi eksperimen dengan desain pre-post test one group yang dilakukan selama bulan September-Oktober2021 di RSU Bangil dengan populasi 42 orang yang diambil dengan cara acak dengan memenuhi kriteria inklusi dan eksklusi. Jumlah sampel sebanyak 30 orang dengan menggunakan visual analogue scale (VAS) sebagai alat ukur. Pemberian TENS dengan frekuensi 5 Hz, intensitas 30mA, waktu 20 menit, dan dosis latihan CKC sebanyak 3 set, 10 kali repetisi/set dengan jeda istirahat 15 detik/set selama 4 minggu dengan 2x kujungan perminggu. Uji hipotesis yang digunakan Wilcoxon dan diperoleh hasil nilai median pre dan post masing-masing 6.00 dan 5.00, dengan nilai signifikansi 0.000 (<0.05). Maka disimpulkan bahwa kombinasi Transcutaneous Electrical Nerves Stimulation (TENS) dan Closed Kinetic Chain (CKC) berpengaruh pada menurunkan nyeri pada kasus knee osteoarthritis.Kata kunci: osteoarthritis; transcutaneous electrical nerves stimulation; closed kinetic chain